How do consumers differentiate between fresh food stores - Batt, Peter (2015)
In making their decision to purchase fresh food from a retail store, the consumer behaviour literature identifies three key factors: (i) offer quality; (ii) a competitive price; and (iii) convenience. In an effort to reduce the decline in patronage as more fresh produce moves directly from growers to the major chain stores, the Perth Metropolitan Market commissioned an exploratory study to identify how consumers choose between alternative retail stores. Four categories of store were identified: (i) the major supermarkets; (ii) independent supermarkets; (iii) green grocers; and (iv) grower direct markets. Results reveal that for the major supermarkets, all three factors: quality, competitive price and convenience were rated equally, implying a one-stop shop. For the independent supermarkets, which are primarily located closer to the consumers' place of residence, convenience was the key determining variable. For the independent green grocers and grower direct markets, superior quality and a wide range of product was most important. While consumers generally purchase 80% of the fresh produce they consumed from their preferred place of purchase, convenience was identified as the main reason to purchase from another retail store.